Respiratory behavior of swimmers using a spirometric snorkel system - Götz, J. K.; Sperling, W.; Schlicht, K.; Hartmann, U. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In front crawl swimming, the timing and duration of breathing, especially for inspiration (Ins), highly depends on the swimming motion. If a snorkel is used, this constraint is canceled. Therefore, it is relevant to know whether the coupling between respiration and swimming movement (CRM), while swimming with the snorkel system, keeps equal or changes to arbitrary breathing. The aim of this study is to investigate the respiratory behavior using a snorkel system for gas analysis in swimming front crawl. We want to determine if there are any differences in the CRM at different performance levels of the athletes and if the increase in movement frequency affects the CRM. Furthermore it should be clarified whether the time of Ins is similar to swimming without snorkel. Methods: A total of 17 subjects (12 m/5w; age 17.7±5.4/16.6±3.4 years; height 185.2±7.1/167.0±4.2 cm; weight 73.3±12.9/55.6±6.4 kg) performed a step test swimming front crawl in the swimming flume. They were divided into three groups, elite, juniors and young swimmers. The test started at a speed of 75% of the actual best time in 200 m front crawl (BT2C), followed by a speed increase of 0.05 m/s every minute until subjective exhaustion. In order to collect the flow-volume curve (FVC) the snorkel system MetaSwim (Cortex, Leipzig) was used. The FVC and the swimming movements were simultaneously recorded on video. Using a double-blind video evaluation the last 30 s of each step were analyzed. In the process the FVC was tracked for the duration of Ins and expiration (Exp). Additionally the swimming movement was checked for the duration of the recovery phase of the arm, in which the swimmer inhaled. The duration of the respiratory cycles were compared with those of the movement cycles. Paired t-tests were used for comparison with a 95% level of confidence. Results and Discussion: It could be shown that a CRM was not implemented by all athletes. Differences between movement and breathing cycle amounted up to 0.18-0.60 s. The performance level and the increase of the movement frequency were found not to be relevant factors. It was striking, that for all swimmers, who named their main stroke front crawl a CRM could be shown. With prevailing CRM the time of the start of Ins is comparable to swimming without a snorkel. The duration of Ins in swimming with a snorkel is high significantly longer (p.0.001) than the duration of the recovery phase of the according arm, which can be explained by the increased dead space of the snorkel. It was noticeable that in exception of one, all swimmers with CRM held their breath after Ins. This means that by increasing the movement frequency not only the duration of Ins and Exp was reduced, but also the duration of the breath holding. This was not seen by swimmers with arbitrary breathing.